Ingested lead pellets in waterfowl at the Ouse Washes, England, 1968-73 - Thomas, G J (Wildfowl, 1975)
The incidence of ingested lead pellets in the gizzards of waterfowl shot on the Ouse Washes, England, mainly dabbling ducks, was determined by examining 1,250 gizzards. The highest incidence was in Pintail Anas acuta (10%) and Mallard (Anas platyrhynchos (9%), with lower values in Teal Anas crecca (3%) and Shoveler Anas clypeata (2%). In the case of Teal and Pintail, ingested shot was recorded for the first time in Britain. No pellets were found in Wigeon Anas penelope or in the small samples of Gadwall Anas strepera, Tufted Duck Aythya fuligula, Pochard Aythya ferina and Coot Fulica atra. Snipe Gallinago gallinago and Moorhen Gallinula choropus also ingest lead pellets. In the dabbling ducks, incidence of pellets is probably related to their feeding habits; high if they commonly grub into the substrate and low if they feed mainly on leaf and stem material. Calculations, taking account of the bias that birds suffering from lead poisoning are more easily shot, indicate that the mortality of birds due to lead poisoning at the Ouse Washes is highest in Pintail and Mallard; respectively, at least 5% and 4% of their populations. In the case of the Mallard this is equivalent to the mortality reported in North America. It is estimated that the average annual mortality at the Ouse Washes due to lead poisoning is at least in the order of 400-700 birds.